Hormone use in menopause & male andropause : a choice for women and men - Segal, Sheldon J. (Sheldon Jerome) (Oxford University Press, 2003)
From distinguished figures in fertility and reproduction research, this book answers common questions about menopause and andropause, and hormone resupplement therapy for menopausal women. It offers information about benefits, risks, and prospects for this field. It also covers the climacteric in men, and gives treatment for andropause.